Kondisi Sosial Ekonomi Nelayan Tangkap di Kelurahan Kolakaasi Kabupaten Kolaka - Ashabul Mujaddid; Fentiny Nugroho (Politeknik Kesejahteraan Sosial Bandung, 2021)
The socio-economic conditions of fishermen in Kelurahan Kolakaasi describe work activities, relationships in the community and the use of assets as capital in developing capacity. They work as fishermen on the “Bagan Ship” which operates for a period of 3 to 4 months at the sea. This research uses qualitative methods with descriptive types. In-depth interviews were conducted using purposive sampling technique. The informant criteria is fishermen who are floating chart owners and fishermen laborers. The results showed that the fishermen's socio-economic conditions were described by several components. First, the work operational situation of fishermen shows the use of “Bagan ships” as operational vessels and control of fishing gear while at the sea. Second, the existence of productive work skills by relying on work commitments and the physical and mental abilities of fishermen while in the work operational area. Third, there are fishermen groups to do self-help. And fourth, there is economic capital for fishermen in the form of income and management as an asset.